2008
DOI: 10.1038/nnano.2008.267
|View full text |Cite
|
Sign up to set email alerts
|

CMOS-compatible fabrication of room-temperature single-electron devices

Abstract: Devices in which the transport and storage of single electrons are systematically controlled could lead to a new generation of nanoscale devices and sensors. The attractive features of these devices include operation at extremely low power, scalability to the sub-nanometre regime and extremely high charge sensitivity. However, the fabrication of single-electron devices requires nanoscale geometrical control, which has limited their fabrication to small numbers of devices at a time, significantly restricting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 29 publications
1
90
0
Order By: Relevance
“…[7][8][9] These devices could form the basis of a new generation of processing information systems, although severe fabrication challenges have made practical implementations difficult. The experimental characterization and modeling of particular systems are receiving much attention at the elementary device level.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These devices could form the basis of a new generation of processing information systems, although severe fabrication challenges have made practical implementations difficult. The experimental characterization and modeling of particular systems are receiving much attention at the elementary device level.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches for parallel fabrication of nanodevices were also developed by other groups. For example Ray et al reported a CMOS-compatible fabrication of room temperature single-electron devices having source and drain electrodes vertically separated by a thin dielectric film (Ray et al, 2008). Concerning the problem of good and reproducible contacts, T. Dadosh et al (Dadosh et al, 2005) proposed the use of two gold nanoparticles (NPs) to contact a conductive organic molecule in a controlled way (Figure 9).…”
Section: (G) (H)mentioning
confidence: 99%
“…Coulomb blockade (CB)-based devices have been realized in a number of different semiconductor [6], metallic [7,8] and organic materials systems [9,10]. Wafer-scale parallel fabrication of devices showing room temperature single electron effects has recently been demonstrated by Ray et al [11].…”
Section: Introductionmentioning
confidence: 99%